Results of sparing omentum resection in children with apendicular peritonitis - Melnychenko, M.; Gudz, V.; Antonyuk, V. (Journal of Education, Health and Sport, 2018)
Introduction. Among treatment methods of omentitis in children are applied incisions on the altered omentum and its drainage, classical resection, conservative therapy, etc. These methods do not prevent the occurrence of complications at appendicular peritonitis. The choice of the most advanced method of treatment of this disease is currently being debated.Purpose: To improve surgical treatment method of omentitis in children with appendicular peritonitis by sparing resection.Material and methods. The novation group included 36 patients with appendicular peritonitis, in which resection of the destructive omentum was performed according to the developed method. The control group was formed by 78 children, who underwent the classical resection method of the large omentum.Results. Among children of NG, who underwent the primary resection of the inflammatory omentum according to the developed technique, postoperative intra-abdominal infiltration arose at one child, but its course was favorable: the relief of pain syndrome, disappearance of palpated "tumor" and normalization of the total body temperature were in 2 -2.5 times faster compared to the control group, which did not require repeated surgical intervention and resulted in a decrease in the duration of inpatient treatment to 12.1 (2.3) days, respectively.Conclusions. Lack of "unsatisfactory" result in children of the NG indicates the advantage of using the developed method of destructively altered epiploon resection and preventing the development of infiltrates of the abdominal cavity.By using a stepwise resection of a destructively modified large epiploon was possible to minimize blood loss and time of surgical intervention, remove the inflammation cell from the abdominal cavity and prevent the development of postoperative omentitis. Application of the proposed methodology of stepwise sparing resection of inflammatory altered omentum in children with appendicular peritonitis as a way to prevent the formation of omentitis in the postoperative period and its abscess formation, contributed to the implementation of the general pediatric surgery principle - saving attitude to the tissues, thus ensuring "good" direct result in 94,4% cases and no "unsatisfactory" results (p≤ 0.0001).